Abnormal vaginal flora correlates with pregnancy outcomes: A retrospective study from 737 pregnant women. (May 2022) - Wang, Weihong; Hao, Jiatao; An, Ruifang
Abstract: Objective: Abnormal vaginal flora (AVF) is a common cause of vulvovaginal symptoms in women. This study aims to investigate the prevalence of AVF in pregnant women and assess associations between diverse AVF subtypes and pregnancy outcomes. Methods: This study retrospectively collected clinical data of pregnant women who had vaginal flora tests (VFT) between January 2015 and December 2018 in the First Affiliated Hospital of Xi'an Jiaotong University. AVF were defined into different subtypes according to the results of VFT, including bacterial vaginosis (BV), vulvovaginal candidiasis (VVC), aerobic bacteria (AV), cytolytic vaginosis (CV), and trichomoniasis. Pregnancy outcomes included gestational age at delivery, preterm birth (PTB), premature rupture of membranes (PROM), and infant birth weight. Student's t -test and Fisher's exact test was used for analyses using SPSS 22.0. P  < 0.05 was considered as statistical significance. Results: A total of 737 pregnant women were included in this study. Pregnant women in AVF group suffered more PROM than women in normal vaginal flora (NVF) group (18.8% [33/176] vs 10.6% [32/302], P  = 0.012); pregnant women with BV (31.3% [5/16] vs 10.6% [32/302], P  = 0.018) and mixed vaginitis (55.6% [5/9] vs 10.6% [32/302], P  = 0.001) had higher PROM rates than women in the NVF group. In addition, pregnant women in NVF and AVF groups had similar PTB rates (5.0% [15/302] vs 3.5% [32/302], P  = 0.38). Conclusions: AVF, including BV and Mixed vaginitis, augments PROM risk in pregnant women, demonstrating the need for vaginal flora examination during pregnancy.